MANAJEMEN PENDIDIKAN MULTIKULTUR UNTUK MENANAMKAN NILAI-NILAI BUDI PEKERTI (STUDI KASUS DI SMP 1 BANTUL DIY) (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
This reseach is aimed to find out the implementation of the management of multicultural education on characteristic value in SMP 1 Bantul DIY. The implementation is found out through learning, extra curricular, and habitual activities. This research is a qualitative research which is done in SMP 1 Bantul DIY, that is located at Jl Kartini No 44 Bantul. The data collecting technique in the research are interview, observation, and documentation. The data analysis used in this research is qualitative analysis. It is done through data reduction, data presentation, and conclusion. The data validity checking used in this research is the lengthen of the observation, the continuity of the observation, and the data triangulation. The conclusion of this research shows that SMP 1 Bantul holds its education management and integrates multicultural education in learning management to all subjects, extra curricular activities, and habitual activities. The management of multicultural education on characteristic value in SMP 1 Bantul is done through some steps of planning, organizing, actuating, controlling, and evaluating. (1) The planning is done through arranging RKAS (school budget), curriculum (KTSP), and lesson plan (RPP) which are done by all teachers and each lesson plan must include characteristic value. (2) The organizing is done through some coordination and task distribution for all teachers. (3) The actuating is done through learning and teaching activities, extra curricular, and habitual activities. In learning and teaching and extra curricular activities, teacher train, discipline, cooperation, tolerant, and apreciation on differences. In habitual activities, students must obey the school rules and etic values. (4) The controlling is done through monitoring and supervising activities. The monitoring and supervising on teachers are done by the headmaster. The monitoring and supervising on students are done by writing down some misbehaves in school rule record book. (5) The evaluating is done by formal evaluation by teachers and non formal evaluation through evaluation discussion meeting. The evaluation by teachers are attitude mark personality and good behavior mark. The obstacles in carrying out the management of multicultur education are: there are some programs that are done less maximumly and there are some school members that do not support the programs.